Micropatterning: Activated‐Ester‐Type Photocleavable Crosslinker for Preparation of Photodegradable Hydrogels Using a Two‐Component Mixing Reaction (Adv. Healthcare Mater. 2/2015). Issue 2 (January 2015) - Yanagawa, Fumiki; Sugiura, Shinji; Takagi, Toshiyuki; Sumaru, Kimio; Camci‐Unal, Gulden; Patel, Alpesh; Khademhosseini, Ali; Kanamori, Toshiyuki
<x xml:space="preserve">Abstract</x> On page 246 S. Sugiura and co‐workers report a novel crosslinker, namely activated‐ester‐type photocleavable crosslinker, to prepare photodegradable hydrogels. The photocleavable crosslinker is a potentially convenient material for preparing photodegradable hydrogels with biocompatible polymers containing amino moieties (amino‐terminated tetra‐arm poly(ethylene glycol) or gelatin. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>